The compressive strength and failure behaviours of the Alporas foam—effect of different geometric sizes - Idriss, A. N. Md; Kasolang, S.; Maleque, Md. Abdul; Mohd Azhari, M. A. (Springer, 2025)
An experimental work was conducted to determine the compressive strength and failure behaviours of Alporas aluminum foam with different thickness to width (t/w) ratio. The single plate at 40 mm × 40 mm × 12 mm, 30 mm × 30 mm × 12 mm and 20 mm × 20 mm × 12 mm giving the t/w of 0.3, 0.4 and 0.6 were compressed at the static load of 1 mm/min. Under the same testing condition the smallest single plate (20 mm × 20 mm × 12 mm) was compared with another largest combined of two pieces at 40 mm × 40 mm × 24 mm. The ductile property possessed by the structure was evident from the dominant of progressive deformation and crackings. Of all the single plates, the smallest 0.6 t/w one developed the highest specific compressive strength and specific plateau strength of 1.96 MPa/g and 1.55 MPa/g respectively. The lowest recorded specific compressive and plateau strengths were with the largest combined of 2 plates showing both at about 0.19 MPa/g. The specific compressive strength of the smallest single plate sample was 10 times higher than that the largest combined of two plates. The least contained structural defects with the smallest single plate sample size was explained to develop the highest strengths than other samples. The progressive failure averagely between 13 and 58 strain percentages responsible for plateau strength development evidence the Alporas is suitable candidate to be used for safety impact devices combating fatalities or injuries during collision.